Management and Recommendations of Nautical Simulators and Laboratory: Multiple-Site Case Study - Arleiny Arleiny; Yoyok Soesatyo; Erny Roesminingsih (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This study aims to manage laboratory management and nautical simulators at Marine Science Polytechnic of Semarang and Polytechnic of Surabaya. Methods This research uses a multi-status study (multiple-site case study) in two institutions. This study uses interview guide instruments, observation sheets, and a list of documentation studies. The results showed that the laboratory management of Marine Science Polytechnic of Semarang and Polytechnic of Surabaya was said to be good. With qualifications in planning, supervising, managing, supervising laboratories and nautical simulators. Laboratory planning and nautical simulators at Marine Science Polytechnic of Semarang go through 4 (four) stages, the procurement preparation stage, the selection preparation stage, the selection implementation stage, and the contract implementation stage and handover of work results. Meanwhile, planning for laboratories and nautical simulators at Polytechnic of Surabaya is divided into 2 (two), procurement of new goods and maintenance. The findings in this study are emphasized on the results of data collection through interviews and documentation sent by resource persons to researchers. And the conclusion of the study shows that the quality management of both marine Science Polytechnic of Semarang and Polytechnic of Surabaya has been running well according to the procedure.